Evaluation of Fumonisins Contamination using Liquid Chromatography Mass Spectrometry in Corn Samples Collected from Different Locations - Ommi, Sailaja (Asian Journal of Pharmaceutics (AJP), 2022)
The aim of the study was to determine fumonisins (FMS) using liquid chromatography coupled with mass spectrometry in maize. Materials and Methods: FMSs are mycotoxins frequently found in contaminated corn samples. The presence of FMSs in corn samples should be continuously controlled to protect the population form risks associated with its proven toxicity. About 24 corn samples were collected in different locations of Andhra Pradesh such as harvesting area, storage area, and dumping area of godown for determination of contamination by FMSs. Results and Discussion: The retention time of the well-defined peak of FMS B1 and B2 was found 1.15 min and 2.59 min which is similar to the obtained method. Among 24 samples, about 7 corn samples were found positive contamination by FMS when subjected to liquid chromatography-mass spectrometry analysis. The high levels of FMS contamination were found in sample number 7(s-7) which is collected from the dumping area of storage godown. The fungal damaged sample was found B1concentration of 242.11 μg/kg and FB2 of 117.15 μg/kg. The concentration of FB1 is very high in the sample compared to the regulatory guidelines limit. The low amount of FMS is identified in sample number 8(s-8) which is collected from the dumping area and in damaged condition. FB1 concentration was found 15.0 μg/kg. The sample 4(s-4) is found contaminated with FB2 with 15.780 μg/kg concentration. Conclusion: Based on the results, it can conclude that corn samples collected from the dumping area of godown are found more contaminated with mycotoxin (FMS) than the other sample collecting area such as storage area and harvesting area.